A survey of attitudes, beliefs and practice regarding alcohol use and screening in pregnancy: an opportunity for support and education?. (December 2017) - Howlett, Helen; Gray, William K; Dismore, Lorelle; Mackenzie, Shonag; Langley, Kate; Davidson, Catriona; Rankin, Judith
Providing antenatal and postnatal support for women who drink alcohol in pregnancy is only possible if those at risk can be identified. However, screening will only be helpful if women feel comfortable with the method used. We conducted a survey of pregnant women and their partners to investigate self-reported beliefs and practice regarding drinking during pregnancy and the acceptability of screening. Pregnant women and their partners attending antenatal clinics in North-East England were asked to complete a short survey regarding their alcohol consumption in pregnancy, their beliefs about safe levels of alcohol in pregnancy and whether they would be happy to have their blood or their baby's meconium analysed for alcohol biomarkers. The data were summarised using descriptive statistics and thematic analysis. A total of 171 pregnant women and 41 partners participated. Of the pregnant women, 153 (89.5%) felt women should abstain from alcohol consumption, although only 70 (40.9%) reported not drinking in pregnancy. Of 96 women who reported drinking in pregnancy and reported when they stopped, all but six (6.3%) stopped drinking when they found out they were pregnant. Of women and partners who recorded an answer, 177 (87.2%) said they would consent to blood biomarker analysis. Confusion over what level of alcohol is safe and using screening as an opportunity for education and support emerged as key themes from free-text responses. Most women viewed screening for alcohol in pregnancy positively, although its acceptability in the small number of women who continue to drink is unclear.